Electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath and preparation method and application thereof

Through the preparation of electromagnetic rheology polyamide composite materials, combined with components such as polysiloxane, wollastonite, electromagnetic rheology carbon fiber and polyacrylonitrile fiber, the problems of high flexibility, high wear resistance and electromagnetic shielding performance are solved, and the problems of high flexibility, high wear resistance and electromagnetic shielding performance are achieved. High-performance materials suitable for high-end equipment drag chain cable sheath materials.

CN119505524AInactive Publication Date: 2025-02-25HANGZHOU LINAN GUANGDA CABLE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411763729.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ordinary cable sheath materials are difficult to meet the conditions of high flexibility and wear resistance, and the signal transmission quality is degraded under external electromagnetic interference.

Method used

Using electromagnetic rheology polyamide composite materials, the mixture of polysiloxane, wollastonite, electromagnetic rheology carbon fiber, polyacrylonitrile fiber and other components is mixed and granulated to form excellent electromagnetic shielding performance, wear resistance and flexibility characteristics. sheath material.

Benefits of technology

It achieves high flexibility and wear resistance, and has good electromagnetic shielding performance and weather resistance. It is suitable for drag chain cable sheathing materials for high-end equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505524A_ABST
    Figure CN119505524A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of polymer sheath materials for electric wires and cables, and relates to a polyamide composite material for a high-flexibility drag chain cable sheath. The polyamide composite material is prepared from the following components in parts by weight: 0.5 to 0.7 part of polysiloxane, 0.2 to 1.0 part of wollastonite, 0.08 to 0.1 part of electromagnetic rheological carbon fiber, 0.1 to 0.4 part of polyacrylonitrile fiber, 5 to 7 parts of organic silicone oil, 60 to 80 parts of polyamide, 20 to 40 parts of ethylene propylene diene monomer, 1 to 3 parts of polypropylene wax, 1.4 to 2.6 parts of antioxidant and 0.5 to 0.7 part of color masterbatch. The polyamide composite material prepared by the invention has excellent flexibility and wear resistance, can be processed and molded by a common extruder, and can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer sheath materials for drag chain cables and relates to an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath and a preparation method and application thereof. Background Art

[0002] Industrial automation, intelligence and digitalization have promoted the rapid development of high-end equipment such as high-end machine tools and industrial robots; the demand for drag chain cables used for power and signal transmission in these high-end equipment has also continued to grow. During the operation of the equipment, the drag chain cables have been in continuous and frequent reciprocating and bending movements; during the service life of the cables, such movements are measured in millions or tens of millions of times, and there is continuous relative displacement friction between the cable body and the drag chain, and between adjacent cables, which places extremely high demands on the flexibility and wear resistance of the cable sheath material. The main areas of use of highly flexible and wear-resistant cables are rail transit, lifting equipment, elevator equipment, electroplating equipment, oil field, port machinery logistics transportation systems, coal mining machinery, etc. At present, ordinary cable sheath materials cannot meet the requirements of use in these wear-resistant occasions.

[0003] In addition, as the cable is a carrier for signal transmission, electromagnetic radiation pollution in the external environment will reduce the quality of signal transmission. It will also affect the daily operation of the equipment. At present, the functional materials of electromagnetic rheological effect mainly use composite materials of titanium dioxide, molybdenum disulfide and ferroferric oxide. For example, the invention patent CN107987916A discloses a method for preparing a material with shear-thinning electromagnetic rheological properties. The composite material prepared has ferroferric oxide as the core, molybdenum disulfide as the shell and titanium dioxide modified on molybdenum disulfide. The core-shell structure can produce a higher shear yield stress. However, when it is applied to a polymer carrier, it is easy to produce sedimentation due to the large density difference between the particles and the carrier, which limits the commercial application of electromagnetic rheological materials. The application of electromagnetic rheological elastomers in the research of drag chain cable sheath materials is expected to become a means of electromagnetic protection. In recent years, researchers have tried to use material design methods to optimize the magnetic-mechanical-electrical coupling properties of electromagnetic rheological elastomers, such as introducing flax woven fibers, polyurethane sponges, zeolites, etc. into electromagnetic rheological elastomers to improve the mechanical-electrical properties of electromagnetic rheological elastomers. The composite material studied in this application belongs to the category of magnetorheological elastomers and is used in drag chain cable sheaths. Under external electromagnetic interference, it has good wave absorption performance and increased electromagnetic shielding performance. It also has excellent wear resistance, heat resistance, and crack resistance. It can be processed and formed by ordinary extruders and can be recycled and reused. Summary of the invention

[0004] The present invention provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath, which is applied to the polymer sheath material of the drag chain cable to solve the problem that existing ordinary cable sheath materials are difficult to meet the use conditions of high flexibility and high wear resistance. In addition, the sheath material prepared by the present invention has temperature resistance and weather resistance.

[0005] Based on the above objectives, the present application solves this need in the field by preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0006] An electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath comprises the following components: 0.5-0.7 parts of polysiloxane, 0.2-1.0 parts of wollastonite, 0.08-0.1 parts of electromagnetic rheological carbon fiber, 0.1-0.4 parts of polyacrylonitrile fiber, 5-7 parts of silicone oil, 60-80 parts of polyamide, 20-40 parts of EPDM, 1-3 parts of polypropylene wax, 1.4-2.6 parts of antioxidant and 0.5-0.7 parts of masterbatch.

[0007] Furthermore, the wollastonite has a particle size of 4-9 μm and contains 51.75% silicon dioxide and 48.25% calcium oxide.

[0008] Furthermore, the diameter of the electromagnetic rheological carbon fiber is 5-9 μm, and the carbon content of the electromagnetic rheological carbon fiber is more than 95%.

[0009] Furthermore, the organic silicone oil is one of methyl silicone oil, methylethoxy silicone oil and methylvinyl silicone oil.

[0010] On the other hand, a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath comprises the following steps: Step 1: Polysiloxane modification Add wollastonite to toluene to obtain a uniform suspension, add polysiloxane thereto, ultrasonically mix for 3-5 minutes, add polyacrylonitrile fiber and ultrasonically mix for 15-20 minutes; then heat to 85-90°C, react at constant temperature for 8-10 hours, cool, centrifuge, and vacuum dry for 8-10 hours to obtain a gray powder; Step 2: Blending and granulation After the silicone oil and polyamide are mixed and stirred for 8-10 minutes, the gray powder, EPDM rubber, polypropylene wax, antioxidant and masterbatch prepared in the first step are added and mixed evenly at room temperature, and then extruded and granulated to obtain a polyamide composite material.

[0011] Furthermore, the preparation steps of the polysiloxane are: after mixing methacryloxypropyltrimethoxysilane and deionized water, adjusting the pH to 2, hydrolyzing at room temperature for 10 minutes, and drying the hydrolyzed product to obtain polysiloxane.

[0012] Furthermore, the pH adjuster is one of hydrochloric acid, formic acid and acetic acid. Furthermore, the concentrations of hydrochloric acid, formic acid and acetic acid are all 1 mol / L.

[0013] Furthermore, the mass ratio of methacryloxypropyltrimethoxysilane to deionized water is 1-1.3:1-2.

[0014] Furthermore, the working temperature of the extrusion granulation is 175±5°C in zone 1, 185±5°C in zone 2, 195±5°C in zone 3, 200±5°C in zone 4, 200±5°C in zone 5, 200±5°C in zone 6, and 210°C in the die head.

[0015] On the other hand, the present invention protects a drag chain cable sheath material, which is prepared using the polyamide composite material prepared by the present invention and has not only excellent flexibility and wear resistance, but also is not easy to age.

[0016] On the other hand, the present invention provides an application of a polyamide composite material in a drag chain cable sheath. The present invention designs a drag chain cable sheath material, which has high wear resistance, aging resistance and weather resistance. The material is a thermoplastic elastomer material, which can be processed and formed by a common extruder and can be recycled.

[0017] Compared with the prior art, the present invention has the following beneficial effects or advantages: The present invention uses polysiloxane as an additive to cross-link branched methacryloxypropyltrimethoxysilane to form a continuous thin film that migrates to the surface of the sheath material. However, the wear resistance of polysiloxane cannot last long, so polyacrylonitrile fiber, electromagnetic rheological carbon fiber, and wollastonite are used to modify methacryloxypropyltrimethoxysilane. It can also be understood that as a reinforcing agent, polyacrylonitrile fiber has high elasticity, good toughness and strength, which can enhance the flexibility and wear resistance of the sheath material; electromagnetic rheological carbon fiber has excellent thermal conductivity and electrical conductivity. Polyacrylonitrile fiber and electromagnetic rheological carbon fiber are combined in a polysiloxane cross-linked network to form a composite wave-absorbing structure coating, which increases the electromagnetic shielding effectiveness. The obtained polyamide composite material exhibits a unique magnetorheological effect. It broadens the application occasions of drag chain cables.

[0018] In addition to its reinforcing effect, wollastonite can enhance the weather resistance and acid and alkali resistance of the material. The surface of the crushed wollastonite has active groups such as Si-O-Si, Ca-O, Si-O, and Si-OH, which have good compatibility with methacryloxypropyltrimethoxysilane. The branched methacryloxypropyltrimethoxysilane is cross-linked with wollastonite and polyacrylonitrile fiber to form a continuous protective layer on the surface of the sheath material. A strong wear-resistant layer is formed. In addition, the polyacrylonitrile fiber provides the flexibility of the sheath material, improves the lateral and longitudinal wear resistance of the material, and reduces the wear resistance rate.

[0019] The present invention further adopts organic silicone oil to modify polyamide, aiming at improving the incompatibility between polyamide and the matrix, and improving the affinity between the modified polyamide and polysiloxane to form a firm wear-resistant structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Figure A in the middle is a surface scanning electron microscope image of a pure polysiloxane matrix; Figure 1 Figure B is a scanning electron microscope image of the surface after polysiloxane modification in Example 1.

[0021] Figure 2 Figure A in the middle is a scanning electron microscope image of the surface after polysiloxane modification in Example 4; Figure 2 Figure B is a scanning electron microscope image of the surface after polysiloxane modification in Example 5. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is described below in conjunction with embodiments; however, the present invention is not limited to the following embodiments.

[0023] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.

[0024] The experimental methods and detection methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0025] The masterbatch was purchased from Celanese, USA, model POM C 9021 GV1 / 30; the antioxidant was purchased from Shanghai Lingrui Chemical Co., Ltd.; the polyamide was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., with a molecular weight of 394.

[0026] Example 1 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0027] The following steps are involved: Step 1: Polysiloxane modification 1.2 kg of methacryloxypropyltrimethoxysilane and 1.5 kg of deionized water were added to a container and mixed, and hydrochloric acid (1 mol / L) was added dropwise to adjust the pH to 2. The mixture was hydrolyzed at room temperature for 10 min, and the hydrolyzed product was dried in a vacuum oven at 60° C. for 3 h to obtain polysiloxane.

[0028] Take 18kg of toluene and add it to the container. Start the magnetic stirrer, add 0.8kg of wollastonite, and disperse it by ultrasound at room temperature for 30 minutes to obtain a uniform suspension. Then add 0.6kg of the prepared polysiloxane, mix it by ultrasound for 4 minutes, then add 0.09kg of electromagnetic rheological carbon fiber and 0.3kg of polyacrylonitrile fiber and mix it by ultrasound for 20 minutes. Then heat it to 90℃, react at constant temperature for 9 hours, cool it to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3 minutes, and vacuum dry it at 60℃ for 9 hours to obtain a gray powder.

[0029] Step 2: Blending and granulation After mixing 6kg of methyl vinyl silicone oil and 70kg of polyamide for 9 minutes, add 18kg of gray powder prepared in the first step, 30kg of EPDM, 2kg of polypropylene wax, 0.7kg of antioxidant 1076, 0.7kg of antioxidant 300, and 0.6kg of masterbatch into a high-speed mixer, mix at room temperature for 5 minutes, and then discharge into a twin-screw extruder granulator for extrusion granulation. The operating temperature of the twin-screw extruder granulator is 175±5℃ in zone 1, 185±5℃ in zone 2, 195±5℃ in zone 3, 200±5℃ in zone 4, 200±5℃ in zone 5, 200±5℃ in zone 6, and 210℃ in the die to obtain a polyamide composite material.

[0030] Example 2 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0031] The following steps are involved: Step 1: Polysiloxane modification 1 kg of methacryloxypropyltrimethoxysilane and 1 kg of deionized water were added to a container and mixed, and hydrochloric acid (1 mol / L) was added dropwise to adjust the pH to 2. The mixture was hydrolyzed at room temperature for 10 min, and the hydrolyzed product was dried in a vacuum oven at 60° C. for 3 h to obtain polysiloxane.

[0032] Take 17kg of toluene and add it to the container. Start the magnetic stirrer, add 0.2kg of wollastonite, and disperse it by ultrasound at room temperature for 30 minutes to obtain a uniform suspension. Then add 0.5kg of the prepared polysiloxane, mix it by ultrasound for 3 minutes, then add 0.08kg of electromagnetic rheological carbon fiber and 0.1kg of polyacrylonitrile fiber and mix them by ultrasound for 15 minutes. Then heat it to 85℃, react at constant temperature for 8 hours, cool it to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3 minutes, and vacuum dry it at 60℃ for 8 hours to obtain a gray powder.

[0033] Step 2: Blending and granulation After mixing 5kg of methyl vinyl silicone oil and 60kg of polyamide for 8 minutes, add 15kg of gray powder prepared in the first step, 20kg of EPDM, 1kg of polypropylene wax, 0.5kg of antioxidant 1076, 0.9kg of antioxidant 300, and 0.5kg of masterbatch into a high-speed mixer, mix at room temperature for 5 minutes, and then discharge into a twin-screw extruder granulator for extrusion granulation. The operating temperature of the twin-screw extruder granulator is 175±5℃ in zone one, 185±5℃ in zone two, 195±5℃ in zone three, 200±5℃ in zone four, 200±5℃ in zone five, 200±5℃ in zone six, and 210℃ in the die head to obtain a polyamide composite material.

[0034] Example 3 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0035] The following steps are involved: Step 1: Polysiloxane modification 1.3 kg of methacryloxypropyltrimethoxysilane and 2 kg of deionized water were added to a container and mixed, and hydrochloric acid (1 mol / L) was added dropwise to adjust the pH to 2. The mixture was hydrolyzed at room temperature for 10 min, and the hydrolyzed product was dried in a vacuum oven at 60 ° C for 3 h to obtain polysiloxane.

[0036] Take 17kg of toluene and add it to the container. Start the magnetic stirrer, add 1.0kg of wollastonite, and disperse it by ultrasound at room temperature for 30 minutes to obtain a uniform suspension. Then add 0.7kg of the prepared polysiloxane, mix it by ultrasound for 5 minutes, then add 0.1kg of electromagnetic rheological carbon fiber and 0.4kg of polyacrylonitrile fiber and mix it by ultrasound for 20 minutes. Then heat it to 90℃, react at constant temperature for 10 hours, cool it to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3 minutes, and vacuum dry it at 60℃ for 10 hours to obtain a gray powder.

[0037] Step 2: Blending and granulation After mixing 7kg of methyl vinyl silicone oil and 80kg of polyamide for 10 minutes, add 20kg of gray powder prepared in the first step, 40kg of EPDM, 3kg of polypropylene wax, 0.8kg of antioxidant 1076, 1.8kg of antioxidant 300, and 0.7kg of masterbatch into a high-speed mixer, mix at room temperature for 5 minutes, and then discharge into a twin-screw extruder granulator for extrusion granulation. The operating temperature of the twin-screw extruder granulator is 175±5℃ in zone one, 185±5℃ in zone two, 195±5℃ in zone three, 200±5℃ in zone four, 200±5℃ in zone five, 200±5℃ in zone six, and 210℃ in the die head to obtain a polyamide composite material.

[0038] Example 4 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0039] The difference from Example 1 is that the mass ratios of toluene, wollastonite, electromagnetic rheological carbon fiber, polyacrylonitrile fiber and polysiloxane in the modification step of polysiloxane are different. Specifically, the mass ratio of toluene, wollastonite, electromagnetic rheological carbon fiber, polyacrylonitrile fiber and polysiloxane is 16:0.1:0.07:0.09:0.4. Take 16kg of toluene and add it to the container, start the magnetic stirrer, add 0.1kg of wollastonite thereto, and disperse it ultrasonically for 30min at room temperature to obtain a uniform suspension. Then add 0.4kg of the prepared polysiloxane thereto, ultrasonically mix for 4min, add 0.07kg of electromagnetic rheological carbon fiber and 0.09kg of polyacrylonitrile fiber and ultrasonically mix for 20min. Then heat it to 90°C, react at a constant temperature for 9h, cool to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3min, and vacuum dry it at 60°C for 9h to obtain a gray powder.

[0040] Example 5 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0041] The difference from Example 1 is that the mass ratios of toluene, wollastonite, electromagnetic rheological carbon fiber, polyacrylonitrile fiber and polysiloxane in the modification step of polysiloxane are different. Specifically, the mass ratio of toluene, wollastonite, electromagnetic rheological carbon fiber, polyacrylonitrile fiber and polysiloxane is 20:1.2:0.2:0.5:0.8. Take 20kg of toluene and add it to the container, start the magnetic stirrer, add 1.2kg of wollastonite thereto, and disperse it ultrasonically for 30min at room temperature to obtain a uniform suspension. Then add 0.8kg of the prepared polysiloxane thereto, ultrasonically mix for 4min, add 0.2kg of electromagnetic rheological carbon fiber and 0.5kg of polyacrylonitrile fiber and ultrasonically mix for 20min. Then heat it to 90°C, react at a constant temperature for 9h, cool to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3min, and vacuum dry it at 60°C for 9h to obtain a gray powder.

[0042] Example 6 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0043] The difference from Example 1 is that the mass ratio of gray powder, methyl vinyl silicone oil, polyamide, EPDM rubber, polypropylene wax, masterbatch, antioxidant 1076 and antioxidant 300 is 14:4:50:19:0.8:0.4:0.4:0.8. After mixing and stirring 4 kg of silicone oil and 50 kg of polyamide for 9 minutes, add 14 kg of gray powder prepared in the first step, 19 kg of EPDM, 0.8 kg of polypropylene wax, 0.4 kg of antioxidant 1076, 0.8 kg of antioxidant 300, and 0.4 kg of masterbatch into a high-speed mixer, mix at room temperature for 5 minutes, and then discharge into a twin-screw extruder granulator for extrusion granulation. The operating temperature of the twin-screw extruder granulator is 175±5°C in zone 1, 185±5°C in zone 2, 195±5°C in zone 3, 200±5°C in zone 4, 200±5°C in zone 5, 200±5°C in zone 6, and 210°C in the die to obtain a polyamide composite material.

[0044] Example 7 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0045] The difference from Example 1 is that the mass ratio of gray powder, methyl vinyl silicone oil, polyamide, EPDM, polypropylene wax, masterbatch, antioxidant 1076, and antioxidant 300 is 21:8:85:45:4:0.8:0.9:2. After 8kg of silicone oil and 85kg of polyamide were mixed and stirred for 9 minutes, 18kg of gray powder, 45kg of EPDM, 4kg of polypropylene wax, 0.9kg of antioxidant 1076, 2kg of antioxidant 300, and 0.8kg of masterbatch prepared in the first step were added to a high-speed mixer, mixed at room temperature for 5 minutes, and then discharged into a twin-screw extruder granulator for extrusion granulation. The operating temperature of the twin-screw extruder granulator is 175±5℃ in zone 1, 185±5℃ in zone 2, 195±5℃ in zone 3, 200±5℃ in zone 4, 200±5℃ in zone 5, 200±5℃ in zone 6, and 210℃ in die head to obtain a polyamide composite material.

[0046] Example 8 The present embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a highly flexible drag chain cable sheath. The difference from Example 1 is that the raw material wollastonite is replaced with talcum powder. Take 18kg of toluene and add it to a container, start the magnetic stirrer, add 0.8kg of wollastonite thereto, and disperse it ultrasonically for 30 minutes at room temperature to obtain a uniform suspension. Then add 0.6kg of the prepared polysiloxane, ultrasonically mix for 4 minutes, and then add 0.3kg of polyacrylonitrile fiber and ultrasonically mix for 20 minutes. Then heat it to 90°C, react at a constant temperature for 9 hours, cool it to room temperature, centrifuge the reaction solution at room temperature at 12000r / min for 3 minutes, and vacuum dry it at 60°C for 9 hours to obtain a gray powder.

[0047] Example 9 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath.

[0048] The difference from Example 1 is that the raw material polyacrylonitrile fiber is replaced with polyimide fiber, 18 kg of toluene is added to the container, a magnetic stirrer is started, 0.8 kg of wollastonite is added thereto, and a uniform suspension is obtained by ultrasonic dispersion at room temperature for 30 minutes. Then 0.6 kg of the prepared branched methacryloxypropyltrimethoxysilane is added thereto, ultrasonically mixed for 4 minutes, and then 0.3 kg of polyimide fiber is added and ultrasonically mixed for 20 minutes. Then the temperature is raised to 90°C, the reaction is carried out at a constant temperature for 9 hours, and the reaction solution is cooled to room temperature. The reaction solution is centrifuged at room temperature for 3 minutes at 12000 r / min, and vacuum dried at 60°C for 9 hours to obtain a gray powder.

[0049] Example 10 This embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a highly flexible drag chain cable sheath. The difference from Example 1 is that the raw material does not include wollastonite, 18 kg of toluene is added to the container, a magnetic stirrer is started, and then 0.6 kg of the prepared polysiloxane is added thereto, ultrasonically mixed for 4 minutes, and then 0.3 kg of polyacrylonitrile fiber is added and ultrasonically mixed for 20 minutes. Then the temperature is raised to 90 ° C, the reaction is carried out at a constant temperature for 9 hours, and then cooled to room temperature. The reaction solution is centrifuged at room temperature at 12000 r / min for 3 minutes, and vacuum dried at 60 ° C for 9 hours to obtain a gray powder.

[0050] Embodiment 11 The present embodiment provides a method for preparing an electromagnetic rheological polyamide composite material for a highly flexible drag chain cable sheath. The difference from Example 1 is that the raw material does not include polyacrylonitrile fiber, 18 kg of toluene is added to the container, the magnetic stirrer is turned on, 0.8 kg of wollastonite is added thereto, and a uniform suspension is obtained by ultrasonic dispersion for 30 minutes at room temperature. Then 0.6 kg of the prepared polysiloxane is added thereto, and ultrasonic mixing is performed for 4 minutes. Then the temperature is raised to 90 ° C, the reaction is carried out at a constant temperature for 9 hours, and the reaction solution is centrifuged at room temperature for 3 minutes at 12000 r / min, and vacuum dried at 60 ° C for 9 hours to obtain a gray powder.

[0051] The testing indicators of the polyamide composite material prepared by the present invention are specifically shown in Table 1.

[0052] Table 1 Table 2 From Table 1, it can be seen that the performance of Examples 1-3 is better than that of Examples 4-7, and the wear resistance test of Examples 8-11 does not meet the wear resistance test standard (≥150), and the flexibility radius is lower than the conventional 7.5×. It can be concluded that the proportion of each component in the materials of Examples 1-3 is the best. The present invention uses wollastonite, polyacrylonitrile fiber and branched methacryloxypropyltrimethoxysilane, which greatly improves the flexibility and wear resistance of the sheath material. Figure 1 As can be seen from Figure A, pure polysiloxane presents a smooth surface structure under a scanning electron microscope. In Figure B, after the polysiloxane is modified, wollastonite and polyacrylonitrile fibers are added to the polysiloxane. Fine polyacrylonitrile fibers are observed on the surface of the material, evenly distributed in the polysiloxane matrix. The surface of the material is dense, without agglomeration of large wollastonite particles, and no defects or cracks exist. Figure 2Figures A and B in the middle are surface scanning electron microscope images obtained by changing the mass ratio of toluene, wollastonite, polyacrylonitrile fiber, and polysiloxane in the present application. The performance of the polyamide composite material obtained in Example 4 and Example 5 cannot meet the use standard of the drag chain cable sheath. From the surface electron microscope image, it can be seen that wollastonite and polyacrylonitrile fiber are unevenly distributed in the polysiloxane matrix, and there are agglomerations and defects. This proves that the modified polysiloxane in the present application forms a continuous wear-resistant protective layer on the surface of the sheath, and its flexibility and wear resistance are greatly improved.

[0053] The thermoplastic elastomer sheath material studied in the present invention has been preliminarily applied to the sheath of the drag chain cable, and the obtained drag chain cable has high flexibility and high wear resistance, which is better than the ordinary drag chain cable sheath on the market. The use of other inorganic reinforcing agents or fibers cannot achieve the technical effect of the present invention.

[0054] From the wear resistance test in Table 2, it can be seen that the polyamide sheath material prepared in the present invention has excellent wear resistance, which is much higher than that of ordinary sheath materials. The wear resistance of the thermoplastic sheath materials prepared in Examples 4-11 does not meet the wear resistance test standard of sheath materials (≥150).

[0055] The effective absorption bandwidths of the electromagnetic rheological polyamide composite materials prepared in Examples 1-3 are 2.53 GHz, 2.81 GHz, and 2.51 GHz, respectively, and the corresponding electromagnetic shielding effectiveness are 30.25 dB, 21.20 dB, and 25.92 dB.

[0056] As described above, the present invention can be well implemented. The above embodiments are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention.

Claims

1. An electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath, characterized in that: The invention comprises the following components: 0.5-0.7 parts of polysiloxane, 0.2-1.0 parts of wollastonite, 0.08-0.1 parts of electromagnetic rheological carbon fiber, 0.1-0.4 parts of polyacrylonitrile fiber, 5-7 parts of silicone oil, 60-80 parts of polyamide, 20-40 parts of EPDM rubber, 1-3 parts of polypropylene wax, 1.4-2.6 parts of antioxidant and 0.5-0.7 parts of masterbatch.

2. The electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 1, characterized in that: The particle size of the wollastonite is 4-9 μm.

3. The electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 1, characterized in that: The diameter of the electromagnetic rheological carbon fiber is 5-9 μm.

4. The electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 1, characterized in that: The organic silicone oil is one of dimethyl silicone oil, methylethoxy silicone oil and methylvinyl silicone oil.

5. A method for preparing an electromagnetic rheological polyamide composite material for a high-flexibility drag chain cable sheath, characterized in that: The preparation method comprises the following steps: Step 1: Polysiloxane modification Wollastonite is added to toluene to obtain a uniform suspension, polysiloxane is added thereto, and after ultrasonic mixing for 3-5 minutes, polyacrylonitrile fiber and electromagnetic rheological carbon fiber are added and ultrasonically mixed for 15-20 minutes; then the temperature is raised to 85-90°C, constant temperature reaction is performed for 8-10 hours, cooled, centrifuged, and vacuum dried for 8-10 hours to obtain a gray powder; Step 2: Blending and granulation After the silicone oil and polyamide are mixed and stirred for 8-10 minutes, the gray powder, EPDM rubber, polypropylene wax, antioxidant and masterbatch prepared in the first step are added and mixed evenly at room temperature, and then extruded and granulated to obtain a polyamide composite material.

6. The method for preparing the electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 5, characterized in that: The preparation steps of the polysiloxane are as follows: after mixing methacryloxypropyltrimethoxysilane and deionized water, adjusting the pH to 2, hydrolyzing at room temperature for 10 minutes, and drying the hydrolyzed product to obtain the polysiloxane.

7. The method for preparing the electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 5, characterized in that: The mass ratio of methacryloxypropyltrimethoxysilane to deionized water is 1-1.3:1-2.

8. The method for preparing the electromagnetic rheological polyamide composite material for high-flexibility drag chain cable sheath according to claim 5, characterized in that: The working temperature of the extrusion granulation is 175±5°C in zone 1, 185±5°C in zone 2, 195±5°C in zone 3, 200±5°C in zone 4, 200±5°C in zone 5, 200±5°C in zone 6, and 210°C in the die head.

9. A polymer sheath material for a drag chain cable, characterized in that: The compound is prepared by the preparation method described in any one of claims 5 to 8.

10. Use of the polymer sheath material according to claim 9 in drag chain cables.

Citation Information

Patent Citations

  • Preparation method of material with shear thinning electromagnetorheological property

    CN107987916A

  • High-wear-resistance thermoplastic elastomer sheath material as well as preparation method and application thereof

    CN115895120A

  • Long-carbon-chain polyamide resin composition and continuous fiber reinforced long-carbon-chain polyamide composite material

    WO2022227750A1

  • Flame-retardant carbon fiber reinforced polyamide composite material and preparation method therefor, and preparation method for surface grafted carbon fiber

    WO2023159378A1